Establishing core competencies, opportunities, roles and expertise for oncology social work. (July 2022) - Zebrack, Brad; Schapmire, Tara; Otis-Green, Shirley; Nelson, Krista; Miller, Nina; Donna, Donna; Grignon, Michael
Summary: While oncology social workers are the primary providers of psychosocial services, they vary in what they do and how they work across different cancer care settings. Standards of Practice suggest that there exists a core or universal set of activities and tasks that are grounded in the values and principles of social work and apply across all settings. The purpose of this study was to identify activities that delineate and distinguish Competencies, Opportunities, Roles and Expertise (CORE) for oncology social work. Research was conducted using Concept Mapping, a structured and prescribed approach to collecting, analyzing, and interpreting qualitative and quantitative data while engaging stakeholders in the research process. Findings: An expert panel of oncology social work practitioners, academicians, and leaders in the field (n = 35) generated 91 practice behaviors that were subject to card sorting and ratings of importance. A visual map consisting of six clusters best represented the statistical fit of the data (stress value = 0.18) while maintaining the most meaningful categorization of individual statements. These six domains were as follows: Clinical Assessment and Intervention (38 items; mean importance = 3.31); Professional Advocacy and Political Action (5 items; mean importance = 3.03); Case Management and Care Coordination (16 items; mean importance = 3.02); Patient Education and Advocacy (8 items; mean importance = 2.82); Organizational Support and Service (12 items; mean importance = 2.74); Professional Education (12 items; mean importance = 2.45). Application: These results may inform initiatives related to social work education and training, credentialing and certification, health policy, research and advocacy on behalf of patients, families, communities, and the profession.